Fragmentation of peasant land in Malaysia: transmission mechanisms and role of institutions - Khalid, Haniza (Ministry of Rural Development, National Institute of Rural Development, India, 2018)
The paper discusses aspects of traditional informal credit system and inter-generational land transfers and how they affect landholding structure in the Malaysian rural areas. The formal and informal institutions that supported them inevitably produce various layers of transaction costs and market imperfections in the peasant land market; such that land fragmentation is often the most rational and convenient outcome for the peasant household. The implication of this microlevel decisions is today apparent in the pattern of land-use and land values that Malaysia sees today. In its entirety, the paper should be useful in allowing one to map the right questions to explain today’s agricultural land market while answering yet others such as why current policy measures, in particular those relating to agriculture, fail to effectively address the issue of land fragmentation and decline in agricultural production and hectarage. In addition, we argue that challenges to preservation of economic land sizes vary depending on the land ownership structure i.e. private holdings, group agrarian schemes, land settlement schemes